New relative sea-level (RSL) indications from the Eastern Mediterranean: Middle Bronze Age to the Roman period (~3800-1800 y BP) archaeological constructions at Dor, the Carmel coast, Israel. - Assaf Yasur-Landau; Gilad Shtienberg; Gil Gambash; Giorgio Spada; Daniele Melini; Ehud Arkin-Shalev; Anthony Tamberino; Jack Reese; Thomas E Levy; Dorit Sivan (PLoS ONE, 2021)
This article presents new archaeological observations and multidisciplinary research from Dor, Israel to establish a more reliable relative sea level for the Carmel Coast and Southern Levant between the Middle Bronze Age and the Roman period (ca. 3500-1800 y BP). Our record indicates a period of low relative sea level, around -2.5 m below present, from the Middle Bronze Age to the Hellenistic period (ca. 3500-2200 y BP). This was followed by a rapid rise to present levels, starting in the Hellenistic period and concluding during the Roman period (ca. 2200-1800 y BP). These Roman levels agree with other relative sea-level indications from Israel and other tectonically stable areas in the Mediterranean. Several relative sea-level reconstruction models carried out in the current study provide different predictions due to their parameters and do not model the changes observed from field data which points to a non-isostatic origin for the changes. Long-term low stable Iron Age relative sea level can be seen in Dor, where Iron Age harbor structures remain around the same elevation between ca. 3100-2700 y BP. A similar pattern occurs at Atlit, the Iron Age harbor to the north used continuously from ca. 2900 y BP to the beginning of the Hellenistic period (ca. 2200 y BP). An examination of historical and archaeological sources reveals decline and occasional disappearance of Hellenistic sites along the coast of Israel at ca. 2200 y BP (2nd century BCE), as in the case of Yavneh Yam, Ashdod Yam, Straton's Tower, and tel Taninim. In Akko-Ptolemais, the large harbor installations built in the Hellenistic period were never replaced by a substantial Roman harbor. The conclusions of this research are thus relevant for the sea-level research community and for the historical analyses of the Israeli and South Levantine coastline.